Financial growth and economics development the Philippines - Villanueva, Delano P. (1967)
The financial aspects of economic development have been discussed by Professors John G. Gurley and Edward S. Shaw. This study draws on their contributions for the purpose of explaining the growth of debt, financial assets, and financial institutions in the Philippines over the last decade and a half. The first section briefly presents some concepts and definitions. The second and third discuss the growth of primary securities and the development of financial intermediation. In the final section, the contours of Philippine financial development are summarized and suggestions for further offered. Financial assets accumulate in the course of economic development. These assets are termed "primary securities" if issued by non-financial intermediaries.
Keywords: Economic development -- Philippines; Assets (Accounting); Financial assets; Finance -- Philippines -- 1949-1964; Gross national product